2015
DOI: 10.1515/jppr-2015-0010
|View full text |Cite
|
Sign up to set email alerts
|

Aphid migrant activity in refuge habitats of the Wielkopolska agricultural landscape

Abstract: Refuge habitats have a stabilising effect on the entomofauna in the agricultural landscape. The objective of this research was to follow the migrant activity of aphids in two types of refuge habitats: shrubs and roadsides of rural areas. Moericke traps method were used for testing the seasonal activity of aphids. The dynamics of species numbers were assessed, and the phenology of the dominating taxa was examined. From 2008 to 2010, more than 5,000 winged aphids from 94 species were caught in shrub habitats, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 31 publications
0
5
0
1
Order By: Relevance
“…All studies except Ditsworth et al [108], Freitag et al [109] and Wilkaniec et al [113] reported no statistically significant differences between the biodiversity of verges and those of the compared similar habitats for at least one of their comparisons. However, Ditsworth et al [108] reported that a power line corridor hosted more individuals of Cicadellidae, Aphididae, Lepidoptera and Thysanoptera than pynion-juniperus woodland.…”
Section: Question #2: Is the Biodiversity Of Lti Verges Equal To Higher Or Lower Than The Biodiversity Of Habitats Away From The Lti?mentioning
confidence: 97%
See 2 more Smart Citations
“…All studies except Ditsworth et al [108], Freitag et al [109] and Wilkaniec et al [113] reported no statistically significant differences between the biodiversity of verges and those of the compared similar habitats for at least one of their comparisons. However, Ditsworth et al [108] reported that a power line corridor hosted more individuals of Cicadellidae, Aphididae, Lepidoptera and Thysanoptera than pynion-juniperus woodland.…”
Section: Question #2: Is the Biodiversity Of Lti Verges Equal To Higher Or Lower Than The Biodiversity Of Habitats Away From The Lti?mentioning
confidence: 97%
“…• "unwanted species" (invasive species, pests…) along roads (group f ) [101][102][103][104][105][106][107]. • other taxa along terrestrial LTIs (group g) [49,67,90,91,100,[108][109][110][111][112][113]. • various taxa along waterways (group h) [114][115][116].…”
Section: Question #2: Is the Biodiversity Of Lti Verges Equal To Higher Or Lower Than The Biodiversity Of Habitats Away From The Lti?mentioning
confidence: 99%
See 1 more Smart Citation
“…It was found for the first time in 2002 in Southern Poland (Cichocka and Lubiarz 2003), and three years later recorded in Poznań from P. cerasifera (Wilkaniec and Wilkaniec 2013). Since then, the species has been constantly collected from various objects of urban green areas in Poznań (Wilkaniec et al 2015(Wilkaniec et al , 2016.…”
Section: Discussionmentioning
confidence: 99%
“…Aphids can show different responses to different habitats such as agricultural, nonagricultural, urban and landscape areas in terms of their diversity, species richness, abundance, plant interactions and diversity of natural enemies (Janković et al, 2017;Kök et al, 2020;Barczak et al, 2021). Also, non-crop contexts such as stubble and pasture areas, roadsides, urban and landscape areas are important as refuge habitats for aphids with a migratory life cycle (Wilkaniec et al, 2015). Among these areas, lagoons are defined as semi-connected coastal ponds located on the edge of seas with a large coastal zone; they are also considered as geographical heritage due to their rare geomorphological formations (Kocataş, 1999;Doğaner, 2003).…”
Section: Introductionmentioning
confidence: 99%